The Routledge Companion to Radio and Podcast Studies - Lindgren, Mia; Loviglio, Jason (Taylor & Francis, 2022)
This comprehensive companion is a much-needed reference source for the expanding field of radio, audio, and podcast study, taking readers through a diverse range of essays examining the core questions and key debates surrounding radio practices, technologies, industries, policies, resources, histories, and relationships with audiences. Drawing together original essays from well-established and emerging scholars to conceptualize this multidisciplinary field, this book's global perspective acknowledges radio's enduring affinity with the local, historical relationship to the national, and its unpredictably transnational reach. In its capacious understanding of what constitutes radio, this collection also recognizes the latent time-and-space shifting possibilities of radio broadcasting, and of the myriad ways for audio to come to us 'live.' Chapters on terrestrial radio mingle with studies of podcasts and streaming audio, emphasizing continuities and innovations in form and content, delivery and reception, production cultures and aesthetics, reminding us that neither 'radio' nor 'podcasting' should be approached as static objects of analysis but rather as mutually constituting cultural forms. This cutting-edge and vibrant companion provides a rich resource for scholars and students of history, art theory, industry studies, journalism, media and communication, cultural studies, feminist analysis, and postcolonial studies.